Operational Efficiency Factors Affecting Profitability of the Companies of the Agricultural and Food Industry Group Listed on the Stock Exchange of Thailand: Food and Beverage Sectors - Chantanasiri, Supatra (Journal of Multidisciplinary in Humanities and Social Sciences, 2022)
The purposes of this research article on efficiency factors affecting profitability of listed companies in the agricultural and food industry sector, food and beverage category, were to: 1) study the relationship between financial performance ratios and profitability financial ratios; and 2) study the influence of operating efficiency ratios on profitability ratios. This research was conducted by examining the financial statements of 41 companies in the agricultural and food industries listed on the Stock Exchange of Thailand, especially in the food and beverage sectors, for 3 years (2018-2020). The performance ratios include the liquidity ratio, debt service coverage ratio, and operating performance ratio. The profitability ratios include gross profit margin, net profit ratio, return on assets ratio, and return on equity ratio. In the statistical analysis of the data, the researcher used 3 software packages for processing social science research. First, descriptive statistics were used to describe the percentages of sample data. Second, correlation analysis was utilized to test the correlation coefficient between independent variables and dependent variables. Third, the researcher employed multiple regression analysis to determine the influence of independent variables on dependent variables. The results showed that the financial performance ratios were influential and correlated with profitability. Moreover, it was discovered that the debt-to-asset ratio influenced profitability. The interest coverage ratio was also found to be related to the net profit ratio, the return on assets ratio, and the return on equity ratio. In addition, the study revealed that the inventory turnover ratio was related to and influenced the gross profit ratio, the net profit ratio, the return on assets ratio, and the return on equity ratio.